Knowledge management practices and technologies in higher education institutions [Prácticas y tecnologías de gestión del conocimiento en instituciones de educación superior] - Varvakis, G. (2017)
Higher Education Institutions (HEI) implement Knowledge Management (KM) strategies to improve educational services. KM practices, supported by web 2.0 technologies, allow the identification, creation, storage, interchange and use of knowledge. The aim of this article is to assess the use of such practices and technologies in HEIs, based on data from one case study. Results show that KM practices and web 2.0 technologies are known but seldom used in HEIs. The article concludes by suggesting that action plans aiming at institutionalizing KM practices must go in line with an overall KM strategy, involving the whole organization.